Implementación de una empresa de servicio de limpieza y mantenimiento de hogares en la ciudad de Guayaquil - Garay Cordero, Alexandra Alicia (2011)
The city of Guayaquil has at present a consumer demand for cleaning and maintenance unsatisfied. The general mission of this project is to demonstrate the economic viability to implement a cleaning and maintenance services to homes in the city of Guayaquil. The name of our company will be "Deep Clean House", a home maintenance professional will complete the job to the highest of standards, meaning that you can be confident that your home is safe, clean, and looks as good as it possibly can in addition leaving you more time for the better things in life. The main objective of “Deep Clean House” is to satisfy the requirements and demands of the customer with excellent machinery and labor. To finance this project, we hope count with own resources of the partners and a loan to a bank. The Net Present Value of the project is positive, it should be accepted.